Festival and Urban Identity: A Case Study of the Malang Flower Carnival in Yogyakarta - Kumoro, Nindyo Budi; Apriwan, Franciscus; Maghfiroh, Lailatul; Albahri, Abdul Charis (Humaniora, 2024)
Cultural festivals, often called carnivals, events, or celebrations, have become prominent showcases across Indonesia, particularly in the post-New Order period. These festivals serve two main objectives: promoting tourism and reviving regionalism as well as traditional identities in response to past centralization policies. This study examines the Malang Flower Carnival (MFC) in Malang City, East Java, which has been a key feature of the city's cultural landscape since 2010. In 2022, the MFC deviated from its tradition by participating in the Jogja Fashion Carnival in Yogyakarta instead of holding its own event in Malang. This shift provides a unique opportunity to analyze how Malang's cultural identity is represented to an audience in another city. The findings suggest that while the MFC captivated visitors with its elaborate costumes, it struggled to convey the intended narrative of Malang's cultural identity. This difficulty stems from the complexity of representing Malang's multiple identities—rooted in its historical legacy, contemporary identity as the "City of Flowers," and broader regional narratives. The themes of bravery and heroism, although recognized, were often disconnected from Malang's broader historical and cultural context